2019
DOI: 10.1016/j.aquaculture.2018.09.006
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of European eel sperm cryopreservation protocols with standardization as a target

Abstract: The critical situation of the European eel (Anguilla anguilla) has urged the development of sperm cryopreservation protocols for reproduction in captivity and cryobanking. In the last years, two research groups have developed their own protocols in Spain and Hungary with positive results, but difficult to compare. Here, a series of experiments were conducted to test the quality of thawed sperm after using both protocols, determining which of them produce the best results and aiming for standardization. The qua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
24
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
2
2
2

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(27 citation statements)
references
References 39 publications
3
24
0
Order By: Relevance
“…Furthermore, the use of methylated cryoprotectants is known to induce the production of reactive oxygen species (ROS) that can cause several damages, such as cytosine methylation in fish spermatozoa DNA (Kawai et al, 2010), which is one of the principal epigenetic mechanisms (Bird, 2002), and have been suggested to be a good indicator for sperm quality (Herráez et al, 2017), affecting consequently the success of a cryopreservation protocol. In this comparative study, Herranz-Jusdado et al (2019a) showed that the protocol using methanol, initially developed by the Hungarian group (Müller et al, 2012;Szabó et al, 2005), was better in terms of higher spermatozoa viability and motility than the protocol with DMSO developed by the Spanish group (Asturiano et al, 2016;Peñaranda et al, 2009). Furthermore, the protocol with DMSO induced a hypo-methylation of them spermatozoa DNA, whereas no changes in DNA methylation were observed when sperm was cryopreserved with the protocol with methanol.…”
Section: European Eel Sperm Cryopreservationmentioning
confidence: 85%
See 4 more Smart Citations
“…Furthermore, the use of methylated cryoprotectants is known to induce the production of reactive oxygen species (ROS) that can cause several damages, such as cytosine methylation in fish spermatozoa DNA (Kawai et al, 2010), which is one of the principal epigenetic mechanisms (Bird, 2002), and have been suggested to be a good indicator for sperm quality (Herráez et al, 2017), affecting consequently the success of a cryopreservation protocol. In this comparative study, Herranz-Jusdado et al (2019a) showed that the protocol using methanol, initially developed by the Hungarian group (Müller et al, 2012;Szabó et al, 2005), was better in terms of higher spermatozoa viability and motility than the protocol with DMSO developed by the Spanish group (Asturiano et al, 2016;Peñaranda et al, 2009). Furthermore, the protocol with DMSO induced a hypo-methylation of them spermatozoa DNA, whereas no changes in DNA methylation were observed when sperm was cryopreserved with the protocol with methanol.…”
Section: European Eel Sperm Cryopreservationmentioning
confidence: 85%
“…The traditional hormonal treatment with gonadotropins to induce maturation in Japanese eel and European eel males typically consists of weekly injections of human chorionic gonadotropins (hCG) (Ohta et al, 1997;Pérez et al, 2000) and has been used as the preferred method to obtain high quality sperm for cryopreservation trials in the eels (Asturiano et al, 2004;Garzón et al, 2008;Herranz-Jusdado et al, 2019a;Müller et al, 2004;2012;Peñaranda et al, 2009;Szabó et al, 2005;Tanaka et al, 2002a). However, application of heterologous hormonal treatments with hCG have been observed to produce low rates of fertilization and hatching due to low gamete quality (Tanaka et al, 2002a), and a new line of studies focuses on the development of homologous gonadotropic hormones to induce eel maturation.…”
Section: Eels Artificial Maturationmentioning
confidence: 99%
See 3 more Smart Citations